COMPETENCY ANALYSIS OF AUDITORS WHO HAVE RELATIVES WITH PARTNERS IN PRODUCING QUALITY AUDITS AT PUBLIC ACCOUNTING FIRMS IN BANDUNG - Sutrisna, Wawan Asad; Merlina, Tina; Apriyanti, Apriyanti (Accounting Research Journal, 2023)
Abstract. Kinship relations are a homework in itself for business actorsin developing countries to obtain competent workers. The aim of thisresearch is to determine the competency of an auditor who has a relativerelationship with a partner in producing quality audits. This research usesa qualitative method with an ethnomethodological approach in one of thelocal KAPs in the city of Bandung. It is concluded that competenceinfluences the quality of audits at Public Accounting Firms (KAP) in theBandung area. With a very strong and positive correlation category,which means that the better the audit competency, the better the auditquality.Keywords: Auditor Competency, Quality Audit